Pengaruh Konsentrasi Pupuk Organik Cair Dan Dosis Amelioran Terhadap Pertumbuhan Dan Hasil Tanaman Buncis (Phaseolus vulgaris L) - Iyus, Enang; Turmuktini, Tien; Maulana, Agus Surya (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This study aims to study the interaction of Liquid Organic Fertilizer (POC) concentration and amelioran dosage on agronomic characters and yields of chickpea plants. This research was carried out in the experimental field at Winaya Mukti University, Sumedang Regency and was carried out from September 2022 to November 2022 which is located at an altitude of 850 m.asl. The experimental design used in this experiment was a split plot consisting of two factors and repeated twice. The first factor was the concentration of POC which consisted of 4 levels, namely 0 cc L-1, 2 cc L-1, 4 cc L-1 and the second factor was the dose of amelioran which consisted of 4 levels, namely 0 ton ha-1, 0 ton ha- 1, 2 tons ha-1, 4 tons ha-1 and 6 tons ha-1 so that there are 16 treatment combinations. The results of the study only showed an interaction with the number of leaves at the age of 14 HST, while other observational parameters both on the agronomical characters and the yield of chickpea plants did not have an interaction between the concentration of POC and the dose of amelioran. The experimental results showed that no POC dose treatment and the dominant concentration of amelioran had a significant effect on the agronomic characters and yield of bean plants.